Visualization of Multifractal Superconductivity in a Two-Dimensional Transition Metal Dichalcogenide in the Weak-Disorder Regime - Rubio-Verdu, Carmen; Garcia-Garcia, Antonio M.; Ryu, Hyejin; Choi, Deung-Jang; Zaldivar, Javier; Tang, Shujie; Fan, Bo; Shen, Zhi-Xun; Mo, Sung-Kwan; Ignacio Pascual, Jose; Ugeda, Miguel M. (AMER CHEMICAL SOC, 2020)
Eigenstate multifractality is a distinctive feature of noninteracting disordered metals close to a metal-insulator transition, whose properties are expected to extend to superconductivity. While multifractality in three dimensions (3D) only develops near the critical point for specific strong-disorder strengths, multifractality in 2D systems is expected to be observable even for weak disorder. Here we provide evidence for multifractal features in the superconducting state of an intrinsic, weakly disordered single-layer NbSe2 by means of low-temperature scanning tunneling microscopy/spectroscopy. The superconducting gap, characterized by its width, depth, and coherence peaks' amplitude, shows a characteristic spatial modulation coincident with the periodicity of the quasiparticle interference pattern. The strong spatial inhomogeneity of the superconducting gap width, proportional to the local order parameter in the weak-disorder regime, follows a log-normal statistical distribution as well as a power-law decay of the two-point correlation function, in agreement with our theoretical model. Furthermore, the experimental singularity spectrum f(alpha) shows anomalous scaling behavior typical from 2D weakly disordered systems.
Keywords: FLUCTUATIONS; LOCALIZATION; DIFFUSION; ABSENCE; SINGLE; WAVE